Improving the quality of preclinical simulation training for dental students using a new digital real‐time evaluation system. (12th October 2020) - Tang, Lin; Cao, Ye; Liu, Zhongning; Qian, Kun; Liu, Yuhua; Liu, Yunsong; Zhou, Yongsheng
Abstract: Background: With the rapid development of technology, traditional dental education has undergone a transition with the active incorporation of digital technology into curricula. DCARER is a recently developed digital real‐time evaluation system for the digital assessment of student preclinical simulation practice performance. The system provides supplementary feedback on process analysis in addition to an objective final result. This study evaluated the grading validity of the DCARER system and its effect on dental preclinical practice skills training. Methods: Seventy‐three residents of Grade 2018, all of whom had completed their 3‐year term residencies in standardised and systematic training, were recruited into this study to examine the system's grading validity. All performed crown preparations with the adoption of the DCARER system, which generated both process and final scores. Three experts gave their own grade anonymously according to the final work. The differences between the digital system and the expert scores were analysed. In addition, 60 dental students in Grade 4 and 10 dental faculty members were randomly divided into traditional and digital groups. The students in the traditional group prepared the tooth with the guidance of supervisors, whilst the digital group used the DCARER system. After the class, the students' tooth preparations were scored by the same three experts in a blinded manner. The students and faculty members completed two different sets of questionnaires to evaluate the effects of teaching, acceptance, satisfaction, and evaluation accuracy of the digital system and the traditional method. Results: The grading validity assessment showed no significant difference between the tooth preparation scores given by the DCARER system and the experts ( P > .05). The unique process scores given by the DCARER system were weakly correlated with the final scores given by both the digital system and the experts. The main characteristics of the 60 students and 10 faculty members were homogeneous at baseline ( P > .05). The tooth preparations of the traditional group scored significantly lower than those of the digital group ( P < .01). More students in the digital group (93.3%) believed the judgement to be objective than in the traditional group (73.3%). All students guided by the DCARER system (100%) and 80% of students taught in a traditional manner felt that the assessment reinforced the learning process. Faculty members reported that use of the digital system did not significantly increase their workload and reinforced the learning process for the internship. Conclusion: The results presented here indicate the validity of grading using the digital real‐time evaluation system. Students and faculty could benefit from application of the system in tooth preparation practice, which may provide effective clinical interaction training for dental education.